Mechanisms and Therapeutic Potential of Probiotics as Biofilm Disruptors - Adeola, Morenike Omotayo; Ofesi, Anna Onome; Amhanriamhen, Ilegbenose Reuben (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Biofilms, which are structured populations of bacteria encased in a self-produced extracellular polymeric substance (EPS), provide a serious challenge in clinical medicine, industry, and the environment due to their inherent resilience to antimicrobials and host defenses. As the search for effective, non-antibiotic methods to combat biofilms has intensified, there has been considerable interest in probiotics, which are bacteria that offer health benefits when administered in sufficient amounts. This review aims to evaluate the mechanisms, efficacy, and therapeutic potential of probiotics as biofilm-disrupting agents, with an emphasis on their ability to prevent, weaken, or eradicate pathogenic microbial biofilms across clinical and environmental settings. The objectives of this study were to assess the efficacy of different probiotic species and strains in disrupting established biofilms of clinically relevant pathogens such as Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Candida albicans, and others. To evaluate synergistic interactions between probiotics and conventional antimicrobial agents, examining whether combined therapy enhances biofilm eradication or reduces antimicrobial resistance. This study carefully examines the novel role of specific probiotic strains as potent disruptors of biofilms. Among the various mechanisms that probiotics employ is competitive exclusion, the production of antimicrobial substances (bacteriocins, organic acids, hydrogen peroxide), the release of enzymes that degrade biofilms, disruption of quorum sensing (QS), and modification of host immune responses. Probiotics' ability to combat biofilms created by common pathogens such as Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Candida albicans, and oral infections is rigorously assessed. Current and prospective uses in industrial biofouling management, agriculture, and medical domains (wound healing, urinary tract infections, dental caries/periodontitis, gastrointestinal infections) are investigated. Probiotics are a viable, environmentally friendly method of controlling biofilms, and in the age of growing antibiotic resistance, they may be used as an adjuvant or substitute treatment.